THE ECONOMIC IMPACT OF AUTOMATION AND ARTIFICIAL INTELLIGENCE - Abdurahmonov Abdulaziz Maxmudovich (Scholar Express Journals, 2024)
This article explores the profound economic implications of automation and artificial intelligence (AI) on various sectors and labor markets. As advancements in technology continue to accelerate, automation and AI are reshaping the workforce, leading to both opportunities and challenges. The article examines the impact of these technologies on job displacement, productivity, income distribution, and overall economic growth. It also delves into policy considerations and strategies to mitigate potential negative consequences while maximizing the benefits of automation and AI in fostering sustainable economic development
Keywords: Automation; Artificial Intelligence; Economic Impact; Labor Market